Climate Changes and Societal Stability in Iraq: Proposed Measures - Hameed , Muntasser Majeed; Khalaf, Shojaa Mahmoud (Journal of Ecohumanism, 2025)
Iraq is considered one of the countries most susceptible to the negative impacts of climate change. According to international reports, it is classified as among the top five most affected by climate change in the world, leading to economic resource shortages and an increase in water scarcity, which exposes societal stability in Iraq to a threat. This may result in social disintegration and civil conflicts, so climate changes are considered one of the most dangerous crises affecting societal stability in Iraq during this stage. In this context, the research attempts to trace the causes of climate change and their effects on societal stability in Iraq and suggest some necessary measures to confront them in the future. The research sums up the findings of the study, the most important of which is the need to take comprehensive institutional measures to mitigate the harmful effects of environmental degradation, such as the intensity of greenhouse gas emissions, and to develop treatments, such as legislating the necessary laws for water management to ward off immediate and future risks resulting from societal stability due to climate impacts in order to maintain a better level of societal stability.